Biological mechanisms and therapeutic relevance of the gasdermin family. (December 2020) - Xia, Shiyu
Abstract: Innate immunity enables host defense against pathogens and endogenous danger through inflammasomes, which are supramolecular complexes that recognize the threats and activate the immune response. Inflammasome activation often leads to pyroptosis, a highly inflammatory and lytic form of cell death, as a means of killing infected cells and releasing IL-1 family cytokines that communicate with other cells. Dysregulated inflammasome signaling results in a wide range of immune disorders including gout, sepsis, and hepatitis. Discovered as a direct killer molecule in pyroptosis, gasdermin D (GSDMD) is a pore-forming protein that represents a novel family with diverse cellular functions and pathological roles. This review summarizes current opinions in the biological mechanisms and therapeutic values of the GSDM family, particularly of GSDMD. Detailed mechanisms of auto-inhibition and pore formation by the GSDM family are presented, followed by a brief summary of the progress in the development of GSDM-targeting therapeutics.